Transporte de técnicas processuais no âmbito das ações possessórias multitudinárias - Manga, Mariany de Souza (2024)
The procedural protection of collective possession is analyzed through the combination of studies between multitudinous possessory conflicts, structural conflicts and procedural techniques available in the Brazilian legal system, with the objective of verifying the possibility of compatibility and effective transport of procedural techniques in the context of possessory conflicts involving a large number of people, conflicts related to dispute of possession and other collective conflicts, in order to obtain adequate and efficient judicial protection, which effectively allows the resolution of conflicts brought before the Judiciary. To this end, it was necessary to highlight some general ideas about the protection of possession, in order to establish basic premises for the development of the research. The theme of the social function of property and possession was addressed, in order to support the discussion about possessory on possessory protection in general. The main points relating to multitudinous possessory conflicts and conflicts related to dispute over possession were also emphasized. Afterwards, it was found that the multitudinous possessory conflict can be framed as a structural conflict, and from this some techniques of the structural process were highlighted for the identification of those that would enable eventual transport. The possibility of importing and exporting procedural techniques was also evalueted, based on the model of procedural flexibility supported by the Brazilian Code of Civil Procedure of 2015. Finally, it was identified that the techniques compatible with the protected material right can be transported, as a form of procedural adaptation, allowing the creation of a model outline for the procedural treatment of multitudinous possessory conflicts. The research was developed through bibliographic and legislative techniques, through the deductive method, and is linked to the research line Process, Techniques and Protection of Existential and Patrimonial Rights of the Postgraduate Program in Procedural Law of the Federal University of Espírito Santo